FACTORS ASSOCIATED WITH REMAINING FREE FROM FUNCTIONAL LIMITATIONS DESPITE SOCIOECONOMIC ADVERSITY. (11th November 2018) - Kok, A; Stafford, M; Cosco, T D; Huisman, M; Deeg, D J H; Kuh, D; Cooper, R
Abstract: This study aimed to identify factors that protect individuals exposed to lifelong socioeconomic adversity from developing functional limitations in old age. Data from 1, 973 participants in the MRC National Survey of Health and Development (United Kingdom) were used. Functional Limitations was defined as experiencing difficulty with any daily activity. Socioeconomic adversity had three levels based on life course trajectories. We compared psychosocial factors and health-related behaviours between a "resilient" group (high adversity but no functional limitations) and five groups with other combinations of adversity and limitations. Compared to other individuals with high adversity, resilient individuals had higher adolescent self-management, a lower likelihood of smoking, obesity, and childhood illness, and were more often physically active. Marital status and contact frequency were not associated with resilience. Results suggest that a combination of psychological and behavioural characteristics across life is required to be physically resilient in the face of socioeconomic adversity.